2015
DOI: 10.1093/mnras/stv2219
|View full text |Cite
|
Sign up to set email alerts
|

The Historical X-ray Transient KY TrA in quiescence

Abstract: We present deep optical images of the historical X-ray Transient KY TrA in quiescence from which we confirm the identification of the counterpart reported by Murdin et al. (1977) and derive an improved position of α=15:28:16.97 and δ=-61:52:57.8. In 2007 June we obtained I, R and V images, where the counterpart seems to be double indicating the presence of an interloper at ∼1.4 arcsec NW. After separating the contribution of KY TrA we calculate I=21.47±0.09, R=22.3±0.1 and V=23.6±0.1. Similar brightness in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Employing these values, we estimate the mean value of f (Γ, θ) = 9.74 (Fender 2001). Using the above data along with a range of distance to the source as D = 6 − 11 kpc (Hynes et al 2002;Zurita et al 2002), we estimate the observed kinetic jet power to be L obs jet ∼ 3 − 6 × 10 37 erg s −1 .…”
Section: Spectral Signature Of Disc-jet Connection and Estimation Of ...mentioning
confidence: 98%
“…Employing these values, we estimate the mean value of f (Γ, θ) = 9.74 (Fender 2001). Using the above data along with a range of distance to the source as D = 6 − 11 kpc (Hynes et al 2002;Zurita et al 2002), we estimate the observed kinetic jet power to be L obs jet ∼ 3 − 6 × 10 37 erg s −1 .…”
Section: Spectral Signature Of Disc-jet Connection and Estimation Of ...mentioning
confidence: 98%
“…This has been used not only as a very efficient way to distinguish among different populations in the Galactic plane (see e.g. Drew et al 2005;Corradi et al 2008Corradi et al , 2010Wevers et al 2016) but also to identify the missing optical counterpart of BH candidates (Zurita et al 2015). Figure 3 shows the uncalibrated (r − Hα) vs (r − i ) diagram of all the stars observed in the detector FoV and detected in all three filters.…”
Section: Hα Emission In Outburstmentioning
confidence: 99%
“…They have also derived inclination angle as 68 ± 2 • , which is lower than the value reported by others (for example, Wagner et al, 2001). This may be due to their assumption of negligible non-stellar flux contribution in Near-Infrared band (Wagner et al, 2001, Zurita et al, 2002, Khargharia et al, 2013. Our estimated mass is consistent with the value determined by Wagner et al (2001), McClintock et al (2001a and Khargharia et al (2013).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%